Construction of Control Charts for Drinking Water Treatment in Medani Station of Water Purification, Gezira State, Sudan - Ibrahim Mohamed, Sara; Kamaledin Abusabah, Elnour (Gezira Journal of Engineering and Applied Sciences, 2017)
Water  is one of the important natural resources of the earth, one of these resources is surface water. The objective of this study is to construct variable control charts, on data from Wad Medani Station for Water Purification (WSWP), to test the quality of five properties of tap water namely, pH, turbidity, total hardness, residual chlorine and Total Dissolved Solids (TDS). The samples were selected randomly to cover all the year days. Variable control charts (  charts and  charts) were constructed for the five properties,and then fresh 20 samples were taken and analysed, and then plotted on the charts. The average of pH was 8.1, one point of the pH was above the action limit in pH  charts, two points were located below the lower limit, and five points were located above and below the warning limits and the other points were located within the stable limits. The average of turbidity was 35, in turbidity  chart, it was found that the turbidity values varied by an unexpected amount, The average of residual chlorine was 0.2, one point of the residual chlorine was above the action limit in  charts, two points were located above the warning limit and all the other points were located within the stable limits, this indicates that the process is under control. The average of TDS was 170,in  Chart for TDS, most of points were located between upper and lower warning limits, three points were located above the warning limit and two points were located below warning limit, so the process is considered under control. The average of Total Hardness was130, two points of the Total Hardness was above the action limit in  charts, two points were located below the warning limit and the other points were located between upper and lower warning limits, so the process is considered under control.The study recommends the use of quality control charts beside the laboratories tests to monitor the process and study the seasonal change of the quality of the water in the untreated water from the river to the sedimentation basin.